Ten years after Fukushima: Nuclear energy is still dangerous and unreliable - Ben Wealer; Christian R. von Hirschhausen; Claudia Kemfert; Fabian Präger; Björn Steigerwald (DIW Weekly Report, 2021)
The catastrophic accident at the Fukushima Daiichi Nuclear Power Plant on March 11, 2011, revealed unexpected safety risks of nuclear energy once again. It also accelerated the decline of nuclear energy in the international energy sector: Nuclear energy's share of global electricity generation fell from 17 percent in 1996 to 13 percent in 2011 to approximately ten percent in 2019, with a share of primary energy from nuclear at only four percent. In addition to the regular occurrence of major nuclear accidents since 1945, nuclear power plants also experience considerable outages during normal operation: Only 66 percent of the global available capacity for nuclear power has been utilized since the 1970s. There have also been a number of incidents in Germany and its neighboring countries. Although the outages at German nuclear power plants are below the international average, they are nevertheless considerable even for the younger plants. Economic analyses have largely neglected the unreliable availability of nuclear power-so far, many energy and climate models still view nuclear power as an important source in the future. In Germany, the Fukushima major accident accelerated the nuclear phase-out, which is to occur by the end of 2022 in accordance with the Thirteenth Amendment to the Atomic Energy Act (July 2011).
Keywords: L95; Q48; 330; nuclear power; outages; accidents; economics; Europe